The role of livelihood assets in livelihood strategy choice from the perspective of macrofungal conservation in nature reserves on the Qinghai-Tibetan Plateau - Yuqin Liu; Jia Zhou; Hao Cheng; Yike Li; Yu Shen; Lingfan Wan; Shishuai Yang; Guohua Liu; Xukun Su (Global Ecology and Conservation, 2023)
Livelihoods around nature reserve (NRs), which are highly dependent on the harvest of endangered macrofungi (Cordyceps sinensis, Tricholoma matsutake), challenge biodiversity conservation on the Qinghai-Tibetan Plateau (QTP). Previous studies have attempted to capture the impact of rural livelihood assets through the conceptual framework of a sustainable livelihood and a multinomial logit model to find a possible solution. Although communities around NRs face more severe green traps, they are also regions with limited scientific evidence on this topic. We selected 7 NRs on the southeastern edge of the QTP as the study area, where NRs are densely distributed. Data were collected through a household survey and unstructured interviews with administrators, and we quantitatively analyzed the relationship between livelihood assets and livelihood strategies. K-mean cluster analysis related to income sources was used to identify three distinctive livelihood strategies: livestock, nonfarm, and gathering/livestock strategies. The results indicate that human, natural, and financial assets had significant influences on livelihood strategies and that the choice of livelihood strategy varied by livelihood assets. The multinomial logit model showed that enhancing financial and human assets facilitated the adoption of nonfarm strategies, while nature assets enhanced the propensity toward adopting the gathering/livestock strategy. Hence, this research recommends that policy interventions aimed at both endangered macrofungal conservation and livelihood development should give priority to improving the human assets of households living around NRs to achieve sustainable livelihood development.